Influência da sobreposição de polos em máquinas de relutância variável de fluxo axial com núcleo do tipo C - Gomes Filho, Leonardo Ponte Ferreira (2022)
Switched reluctance machines (SRM) have emerged as an alternative to electrical machines with high power density in view of the growing demand for energy and the high cost of rare earth permanent magnets. SRMs have low inertia because they do not have coils or permanent magnets in the rotor, being used in wind energy and electric cars. SRMs can be classified into radial magnetic flux machines (conventional SRMs) and axial magnetic flux machines according to the direction of the magnetic flux. Type C-core Axial Flux Variable Reluctance Machines (SRM-C) feature modular and independent magnetic cores, reducing the length of the magnetic flux path and, consequently, increasing the magnetic flux density. However, the operating condition in a region of high magnetic saturation makes its modeling difficult. This work presents a research proposal on the SRM-C project. An efficient magnetic equivalent circuit (MEC) method is presented for calculating the inductance in the aligned and misaligned positions from the dimensions of the machine and the magnetic material, with or without overlapping poles in the misaligned position. Then, the results are compared with simulations in finite element methods and with experimental results. In addition, the influence of the overlapping poles in the misaligned position is analyzed for the calculation of inductances and electrical power density. A new machine design equation is proposed so that the SRMs do not present overlapping poles in the misaligned position. The simulation and experimental results validate the efficiency of the methodology used to calculate the inductances. Machines with overlapping poles in the misaligned position have a lower slope of the inductance profile and, consequently, a lower power density.